Authority of Law System Formation: Applied Analysis of Legal System Unity - Цуркан-Сайфуліна, Юлія Василівна; Цуркан-Сайфуліна, Ю. В.; Цуркан-Сайфулина, Юлия Васильевна; Tsurkan-Saifulina, Yuliia V.; Дудченко, Валентина Віталіївна; Дудченко, В. В.; Дудченко, Валентина Витальевна; Dudchenko, Valentyna V. (Allied Business Academy, 2018)
Historical system of legal support of unity of legal system and other forms of statehood building was analyzed in the work. Authors point out that law ensures the possibility of socioeconomic and political process regulation based on cooperation of norms, which are called law. Furthermore, gain in legal experience should be the basis of the formation of system, which will reflect basic provisions characteristic for certain area and lifestyle. In the article, this construction is called legal system. Authors point out legal family as supportive element of law system operation in various territories with different conditions and factors of development. Authors demonstrate that there is the difference in understanding the structure and quality ensuring of the legal process during design of the system of legal support of state. The topicality of the study lies in determination of key elements of authority in legal families in the sphere of regulation of social relations. During the analysis of legal systems and their content in contemporary legal families, authors define the novelty of the study, which lies in that there is shown a process of mixing the legal aspects of legal families existence not only on the basis of civil legal system, but also religious, ideological and pure political legal systems. Authors conclude that such a relation enables to stabilize legal system in general and to allow it to develop.

У роботі проаналізовано історичну систему правового забезпечення єдності правової системи та інших форм державотворення. Автори зазначають, що право забезпечує можливість регулювання соціально-економічного та політичного процесу на основі взаємодії норм, які називаються правом. Крім того, набутий юридичний досвід має стати основою формування системи, яка відображатиме основні положення, характерні для певної сфери та стилю життя. У статті ця конструкція називається правовою системою. Автори виділяють правову сім'ю як опорний елемент функціонування правової системи на різних територіях з різними умовами та факторами розвитку. Автори показують, що існує відмінність у розумінні структури та якості забезпечення юридичного процесу при проектуванні системи правового забезпечення держави. Актуальність дослідження полягає у визначенні ключових елементів влади в правових сім'ях у сфері регулювання суспільних відносин. Під час аналізу правових систем та їх змісту в сучасних правових сім’ях автори визначають новизну дослідження, яка полягає в тому, що показано процес змішування правових аспектів існування правових сімей не лише на основі цивільно-правової системи, але також релігійної, ідеологічної та виключно політичної правової системи. Автори приходять до висновку, що таке співвідношення дає змогу стабілізувати правову систему в цілому та дати можливість їй розвиватися.
Tsurkan-Saifulina Yu. Authority of Law System Formation: Applied Analysis of Legal System Unity / Yu. V. Tsurkan-Saifulina, V. V. Dudchenko // Journal of legal, Ethical and Regulatory Issues. - Vol. 21 (SI). - Allied Business Academy, 2018. - 11 p.
Keywords: legal system; authority of law; legal family; social relations; development of law; правова система; авторитет права; правова сім'я; суспільні відносини; розвиток права; Research Subject Categories::LAW/JURISPRUDENCE